The Things Students Do When They Play Truant - Salima, Sulusa Habba; Prasetyo, Ketut; Haidar, Ali (International Journal for Educational and Vocational Studies, 2020)
This study aims to describe what students do when truant in SMPN 1 Tulangan Sidoarjo. This study uses qualitative research methods with a Case Study approach. Researchers conduct this case study research according to the events in the field by observing students who play truant to a coffee shop, to an internet cafe (internet cafe), etc. This study uses in-depth interviews, and uses participant observation methods. The results showed  the reasons students did truant because they felt bored with the lesson, there was no interest in the lesson, the teacher was less creative, and was not comfortable in how to teach, the students' catch ability was low so they chose to play truant from schools and classrooms so that they become left behind in class lessons and grades drop. they play truant in various ways including asking for permission to go to the bathroom during class but will not return to the class and go to a coffee shop, cafeteria, etc. Based on the results of the study it can be concluded that students who play truant have many different ways and their reasons for truant, so that schools should be more concerned with the situation of students, especially when at school and pay attention to them so that truancy action can be reduced by those who make trespass violations and make them their academic grades did not plummet and could improve again.